The Effect of Compensation and Flexible Work on Performance, Through Work-Life Balance and Motivation on Members of the Sub-district Election Committee (PPK) - Ananda, Ade (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of compensation and flexible work on the performance of members of the District Election Committee (PPK) in the Regional Head Election of Berau Regency, by considering the mediating role of work-life balance and motivation. The background of this study departs from the issue of human resource management in ad hoc institutions that have the potential to face policy inconsistencies, limited work standards, and the challenge of high workloads in a short time. This study uses a quantitative approach with an explanatory-associative design, involving all PPK members throughout Berau Regency as respondents (N = 104) through a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed with the help of SPSS.23 and covariance-based SEM modeling using AMOS.23. The results showed that compensation had a positive and significant effect on work-life balance, while flexible work had a positive and significant effect on motivation. However, neither compensation nor flexible work, as well as the two mediators (work-life balance and motivation), were proven to have a significant effect on performance. Thus, improving performance is not enough just by improving the compensation system or work flexibility, but requires a more comprehensive approach, including strengthening recruitment standards, technical training, leadership, and psychosocial support. These findings enrich the literature related to HR management in ad hoc task-based public organizations, while providing practical implications for the Berau Regency KPU to optimize strategic factors that can drive PPK performance more effectively.